Synthesis method of solid electrolyte and carbon composite coated lithium-rich manganese-based positive electrode material
By forming an island-like carbon composite layer and a solid electrolyte layer on the surface of the lithium-rich manganese-based material, the problems of low conductivity of traditional lithium-rich manganese-based materials and easy to fall off are solved, the high conductivity and stability of the material are achieved, and the service life of the battery is extended.
Patent Information
- Application Number
- CN202411801216.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-09
AI Technical Summary
The lithium-rich manganese-based materials prepared by traditional processes have low ionic conductivity and electronic conductivity. During long-term cycles, due to the expansion and contraction stress inside the battery, the cladding layer on the surface of the material is prone to rupture and fall off, resulting in serious attenuation of battery performance.
A synthetic method of solid electrolyte and carbon composite coating of lithium-rich manganese-based positive electrode material is adopted. By forming an island-like carbon composite layer on the surface of the lithium-rich manganese-based material, and further covering the solid electrolyte layer on the surface, a porous structure and lithium lanthanum titanium chromium oxide coating layer are formed to enhance the conductivity and stability of the material.
The ionic conductivity and electronic conductivity of lithium-rich manganese-based materials are improved, the stability of the material is enhanced, the shedding phenomenon of the cladding layer is reduced, the service life of the battery is extended, and the capacity retention rate is shown in the large-scale charge and discharge test.
Smart Images

Figure BDA0005178094080000101
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of secondary battery materials, and more specifically, relates to a method for synthesizing a solid electrolyte and carbon composite coated lithium-rich manganese-based positive electrode material. Background Art
[0002] Lithium-rich manganese-based cathode material is a lithium-ion battery cathode material with high energy density potential. It is considered to be a strong candidate for the next generation of lithium-ion battery cathode material due to its high specific capacity, low cost and environmental friendliness.
[0003] Compared with traditional lithium iron phosphate materials or nickel cobalt manganese oxide materials, lithium-rich manganese-based materials have a higher working voltage, which can reach 4.5V or even higher. The reason why the working voltage of lithium-rich manganese-based positive electrode materials is relatively high is mainly related to their unique electrochemical activity. This material can be regarded as composed of two components, Li2MnO3 and LiMO2. Within 4.5V, the valence of nickel and cobalt in the traditional layered structure LiMO2 increases, while the lithium ions in the conventional layered structure are removed from the positive electrode and embedded in the negative electrode, and some lithium ions in the Li2MnO3 layer are also removed and enter the layered structure. The new platform that appears above 4.5V is attributed to the contribution of the electrochemical activity of the Li2MnO3 layer at high voltage, including the valence change of part of manganese, the loss of part of the structural oxygen to oxygen and the formation of oxygen vacancies, the loss of electrons from -2 valence oxygen to -1 valence oxygen to provide charge compensation, the removal of lithium ions from the transition metal layer to form Li2O and the rearrangement of the material structure to the traditional layered structure, and the complex charge compensation relationship between lithium, manganese and oxygen. This unique electrochemical activity and charge compensation mechanism enables the lithium-rich manganese-based cathode material to operate at a higher voltage, thereby providing a higher operating voltage.
[0004] However, for lithium-rich manganese-based materials, the material itself has low ionic / electronic conductivity and therefore exhibits poor rate performance. The rate performance of lithium-rich manganese-based positive electrode materials is closely related to their kinetic properties, including the Li+ ion diffusion rate of the material itself and the transfer rate at the electrode / electrolyte interface. The low intrinsic lithium ion diffusion coefficient of the Li2MnO3 phase in the lithium-rich manganese-based positive electrode material also severely restricts its rate performance. Therefore, how to improve the rate performance of the material at the raw material level is one of the technical difficulties faced by technicians in this field. Summary of the invention
[0005] The technical problem to be solved by the present invention is: for the lithium-rich manganese-based materials prepared by traditional processes, their ionic conductivity and electronic conductivity are low. Although they can be improved by coating on the surface, the inventors found that due to the expansion and contraction stress inside the battery during long-term cycles, the continued existence of this stress will cause the coating layer on the surface of the material to easily break and fall off during long-term cycles, resulting in serious degradation of battery performance and the inability to effectively guarantee the service life of the product. Based on the above difficulties, the present invention provides a method for synthesizing a solid electrolyte and carbon composite coated lithium-rich manganese-based positive electrode material.
[0006] The purpose of the present invention is to provide a method for synthesizing a solid electrolyte and carbon composite coated lithium-rich manganese-based positive electrode material.
[0007] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0008] A method for synthesizing a solid electrolyte and carbon composite coated lithium-rich manganese-based positive electrode material, the specific synthesis steps comprising:
[0009] Lithium-rich manganese-based materials coated with island-shaped carbon composite layers:
[0010] By weight, take 100-120 parts of anhydrous ethanol, 4-6 parts of glycerol, 4-6 parts of aluminum nitrate, 0.4-0.6 parts of conductive carbon, and 38-45 parts of lithium-rich manganese-based material;
[0011] First, mix anhydrous ethanol and glycerin evenly, then add aluminum nitrate, stir and dissolve, then add conductive carbon, ultrasonically disperse evenly, then add lithium-rich manganese-based material, heat and stir to concentrate, so that the anhydrous ethanol evaporates, and obtain concentrated material;
[0012] In the above steps, anhydrous ethanol is used as the main solvent and a certain amount of glycerol is added as an auxiliary. First, under the action of anhydrous ethanol, aluminum nitrate is dissolved, and during the concentration process, the aluminum-containing component is gradually deposited on the surface of the lithium-rich manganese-based material. During the deposition process, thanks to the presence of a small amount of glycerol, the aluminum-containing component and the conductive carbon can obtain a more uniform deposition effect. This is mainly because glycerol has a higher boiling point than ethanol. Therefore, after the rapid evaporation of ethanol, it can still provide a certain amount of fluidity on the deposition surface.
[0013] The concentrated material is transferred into a carbonization furnace, and calcined for 4-6 hours at a temperature of 500-550°C under nitrogen protection, and then cooled and discharged to obtain a calcined material;
[0014] In the carbonization furnace, under high temperature conditions, glycerol further volatilizes or decomposes and does not remain in the system, while the aluminum-containing components decompose to form aluminum oxide components, and together with the conductive carbon, form a uniform deposition layer on the surface of the lithium-rich manganese-based material. Due to the decomposition of the aluminum-containing components and the volatilization or decomposition of glycerol, gas can be generated, and gas diffusion causes the deposition layer to form a porous structure;
[0015] The calcined material is subjected to ultrasonic reaction with a strong alkaline solution, washed with water, and dried to obtain a carbon-coated lithium-rich manganese-based material;
[0016] Under the premise of the existence of the aforementioned porous structure, under the action of ultrasound, the strong alkaline solution diffuses and penetrates into the pores, so that most of the exposed aluminum oxide can be corroded and dissolved by the strong alkaline solution. In this process, the part co-coated with the dissolved aluminum oxide is separated from the surface of the lithium-rich manganese-based material, thereby forming an island-shaped coating layer on the lithium-rich manganese-based material. The part that is not dissolved by the strong alkaline solution and the island-shaped coating layer that is still firmly coated on the surface of the lithium-rich manganese-based material under the physical cavitation effect of ultrasound is also difficult to be corroded and dissolved by substances such as HF in the electrolyte, or to be broken under the action of physical stress during the use of the battery, so that the base structure of the product has relatively stable physical and chemical properties;
[0017] Coating a solid electrolyte layer on the surface of the carbon-coated lithium-rich manganese-based material:
[0018] By weight, 100-110 parts of carbon-coated lithium-rich manganese-based material, 6-8 parts of lithium hydroxide, 3-4 parts of titanium sulfate, 1-2 parts of lanthanum nitrate, and 0.8-1.2 parts of chromium sulfate are taken;
[0019] Mixing and dispersing the carbon-coated lithium-rich manganese-based material and water to obtain a main material suspension with a concentration of 100-120 g / L;
[0020] Dissolving lithium hydroxide in water to obtain a lithium hydroxide solution with a mass fraction of 8-10%;
[0021] Add titanium sulfate, lanthanum nitrate and chromium sulfate into water with a mass 10-15 times that of titanium sulfate, and stir to dissolve to obtain a mixed solution;
[0022] The mixed solution is added to the main material suspension, mixed evenly, and then lithium hydroxide solution is added. After heating and stirring for reaction, the mixture is kept warm and allowed to stand, filtered, washed and dried. After being kept warm for 4-6 hours at 700-750°C in a nitrogen atmosphere, the mixture is cooled and discharged to obtain a solid electrolyte and carbon composite coated lithium-rich manganese-based positive electrode material.
[0023] The above technical scheme further begins to deposit a coating layer with excellent lithium ion conductivity on the basis of island coating. Specifically, under the action of the precipitant aluminum hydroxide and accompanied by a high-temperature calcination process, lithium lanthanum titanium chromium oxide compounds are mainly formed in the newly formed coating layer; on the basis of the island coating, the newly formed coating layer can use this as an "anchor point" and gradually fill the gaps between adjacent island coating layers. On the one hand, the surface of the lithium-rich manganese-based material gradually becomes smooth, reducing the specific surface area, and preventing the surface energy from being too high due to excessive specific surface area, causing material dispersion problems during processing, or aggravating surface side reactions, and other problems. At the same time, under the action of the anchor point, the new coating layer can also be firmly adsorbed and fixed on the surface, reducing the occurrence of shedding phenomenon. Finally, the surface composite coating layer has both excellent ionic conductivity and electronic conductivity, and can be firmly adsorbed and fixed on the surface of the lithium-rich manganese-based material.
[0024] Furthermore, the conductive carbon includes the following raw materials in parts by weight:
[0025] 30-40 parts Super P, 8-10 parts single-walled carbon nanotubes, 4-6 parts graphene oxide.
[0026] Furthermore,
[0027] The D50 of the Super P is 40-50nm;
[0028] The single-walled carbon nanotube has an aspect ratio of 3500-4000 and a length of 4-6 μm;
[0029] The D50 of the graphene oxide is 300-350nm;
[0030] The D50 of the lithium-rich manganese-based material is 3-5 μm.
[0031] The above technical solution further combines the conductive carbon of the coating layer material with Super P of different specifications, single-walled carbon nanotubes and graphene oxide. The three can cooperate with each other to form a fast conductive network. The reason why a part of graphene oxide is selected for cooperation and its relatively large particles exist is that during its accumulation process, on the one hand, gaps can be formed between particles, and on the other hand, there are certain gaps inside its layered structure. During the expansion of the battery, the existence of the gap can play a good buffering role, thereby avoiding the collapse of the surface structure.
[0032] Furthermore, the lithium-rich manganese-based material is a quasi-spherical particle, and the sphericity of the lithium-rich manganese-based material is 8.6-8.8.
[0033] By further selecting a lithium-rich manganese-based material with a certain sphericity as the matrix, a uniform deposition layer tends to be formed during the deposition process, reducing excessive or insufficient deposition in local areas, thereby avoiding areas of stress concentration on the surface and avoiding the occurrence of local detachment problems.
[0034] Furthermore, the ultrasonic reaction of the calcined material with a strong alkaline solution comprises:
[0035] The calcined material and the strong alkali solution with a mass fraction of 2-4% are mixed at a mass ratio of 1:8-10, and ultrasonically reacted for 10-15 minutes at a temperature of 40-60°C and an ultrasonic frequency of 60-65kHz;
[0036] Wherein, the strong alkaline solution is selected from any one of sodium hydroxide solution or potassium hydroxide solution.
[0037] Furthermore, the main material suspension also includes acetylene black in an amount of 2-4% by weight of the lithium-rich manganese-based material, and the D50 of the acetylene black is 20-25 nm.
[0038] Furthermore, the main material suspension also includes 1.2-1.4% of the mass of the lithium-rich manganese-based material, carboxymethyl cellulose.
[0039] In addition, the inventors found that when further deposition is performed on the surface of the lithium-rich manganese-based material, if a small amount of acetylene black is added to the main material suspension, it can assist the deposition of the precursor of the lithium lanthanum titanium chromium oxide compound on the surface of the lithium-rich manganese-based material, and it can also be present in the lithium lanthanum titanium chromium oxide compound as a conductive agent in the subsequent process, thereby further improving the conductivity of the product;
[0040] The presence of a small amount of carboxymethyl fiber is conducive to the firm deposition of the precursor on the surface, and in the subsequent anaerobic calcination process, it can gradually decompose and form a carbon skeleton, further enhancing the conductivity and stability of the product. DETAILED DESCRIPTION
[0041] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0042] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0043] The lithium-rich manganese-based material used in the following examples and comparative examples is xLi2MnO3·(1-x)LiNiO2, where x=0.5;
[0044] Example 1
[0045] Lithium-rich manganese-based materials coated with island-shaped carbon composite layers:
[0046] By weight, take 100 parts of anhydrous ethanol, 4 parts of glycerol, 4 parts of aluminum nitrate, 0.4 parts of conductive carbon, and 38 parts of lithium-rich manganese-based material;
[0047] Wherein, the conductive carbon includes the following raw materials in parts by weight:
[0048] 30 parts Super P, 8 parts single-walled carbon nanotubes, 4 parts graphene oxide;
[0049] The D50 of the Super P is 40 nm;
[0050] The single-walled carbon nanotube has an aspect ratio of 3500 and a length of 4 μm;
[0051] The D50 of the graphene oxide is 300 nm;
[0052] The D50 of the lithium-rich manganese-based material is 3 μm;
[0053] The lithium-rich manganese-based material is a quasi-spherical particle, and the sphericity of the lithium-rich manganese-based material is 8.6;
[0054] First, anhydrous ethanol and glycerol are mixed evenly, and then aluminum nitrate is added. After stirring and dissolving, conductive carbon is added. Under the conditions of ultrasonic frequency of 100kHz and temperature of 35°C, ultrasonic dispersion is performed for 2 hours, and then lithium-rich manganese-based materials are added. Subsequently, the mixture is heated and stirred at a temperature of 70°C and a stirring speed of 400r / min to concentrate the mixture so that the anhydrous ethanol is volatilized to obtain a concentrated material.
[0055] The concentrated material was transferred into a carbonization furnace, and heated at a heating rate of 3°C / min under nitrogen protection. After continuous calcination at 500°C for 4 hours, the material was cooled to room temperature with the furnace, and discharged to obtain a calcined material.
[0056] The calcined material and a 2% strong alkali solution were mixed at a mass ratio of 1:8, and ultrasonically reacted for 10 minutes at a temperature of 40°C and an ultrasonic frequency of 60kHz;
[0057] Wherein, the strong alkaline solution is selected from sodium hydroxide solution;
[0058] After the ultrasonic reaction is completed, washing with deionized water until the washing liquid is neutral, and drying to obtain a carbon-coated lithium-rich manganese-based material;
[0059] Coating a solid electrolyte layer on the surface of the carbon-coated lithium-rich manganese-based material:
[0060] By weight, 100 parts of carbon-coated lithium-rich manganese-based material, 6 parts of lithium hydroxide, 3 parts of titanium sulfate, 1 part of lanthanum nitrate, and 0.8 parts of chromium sulfate are taken;
[0061] After mixing the carbon-coated lithium-rich manganese-based material and water, ultrasonically disperse them at an ultrasonic frequency of 65 kHz for 45 minutes, then add acetylene black (2% by weight of the lithium-rich manganese-based material) and carboxymethyl cellulose (1.2% by weight of the lithium-rich manganese-based material), stir and mix them for 60 minutes with a stirrer at a temperature of 65° C. and a rotation speed of 500 r / min to obtain a main material suspension with a concentration of 100 g / L;
[0062] The D50 of the acetylene black is 20 nm;
[0063] Dissolving lithium hydroxide in water to obtain a lithium hydroxide solution with a mass fraction of 8%;
[0064] Add titanium sulfate, lanthanum nitrate and chromium sulfate into water with a mass 10 times that of titanium sulfate, stir and dissolve to obtain a mixed solution;
[0065] The mixed solution is added to the main material suspension, stirred and mixed with a stirrer at a speed of 300 r / min for 30 minutes, and then lithium hydroxide solution is added. The mixture is heated and stirred at a temperature of 80°C and a stirring speed of 600 r / min for reaction for 2 hours, and then kept warm and allowed to stand for 2 hours. The filter cake is collected by suction and washed with deionized water for 3 times, and then dried. After being kept warm and reacted for 4 hours in a nitrogen atmosphere at a temperature of 700°C, the mixture is cooled and discharged to obtain a solid electrolyte and carbon composite coated lithium-rich manganese-based positive electrode material.
[0066] Example 2
[0067] Lithium-rich manganese-based materials coated with island-shaped carbon composite layers:
[0068] By weight, take 110 parts of anhydrous ethanol, 5 parts of glycerol, 5 parts of aluminum nitrate, 0.5 parts of conductive carbon, and 42 parts of lithium-rich manganese-based material;
[0069] Wherein, the conductive carbon includes the following raw materials in parts by weight:
[0070] 35 parts Super P, 9 parts single-walled carbon nanotubes, 5 parts graphene oxide;
[0071] The D50 of the Super P is 45 nm;
[0072] The aspect ratio of the single-walled carbon nanotube is 3800, and its length is 5 μm;
[0073] The D50 of the graphene oxide is 320 nm;
[0074] The D50 of the lithium-rich manganese-based material is 4 μm;
[0075] The lithium-rich manganese-based material is a quasi-spherical particle, and the sphericity of the lithium-rich manganese-based material is 8.7;
[0076] First, anhydrous ethanol and glycerol are mixed evenly, and then aluminum nitrate is added. After stirring and dissolving, conductive carbon is added. After ultrasonic dispersion for 3 hours at an ultrasonic frequency of 110kHz and a temperature of 38°C, a lithium-rich manganese-based material is added. Subsequently, the mixture is heated and stirred at a temperature of 72°C and a stirring speed of 400r / min for concentration to volatilize the anhydrous ethanol, thereby obtaining a concentrated material.
[0077] The concentrated material was transferred into a carbonization furnace, and heated at a heating rate of 4°C / min under nitrogen protection. After continuous calcination at a temperature of 520°C for 5 hours, the material was cooled to room temperature with the furnace, and the calcined material was obtained.
[0078] The calcined material and a 3% strong alkali solution were mixed at a mass ratio of 1:9, and ultrasonically reacted for 12 minutes at a temperature of 50°C and an ultrasonic frequency of 62kHz;
[0079] Wherein, the strong alkaline solution is selected from sodium hydroxide solution;
[0080] After the ultrasonic reaction is completed, washing with deionized water until the washing liquid is neutral, and drying to obtain a carbon-coated lithium-rich manganese-based material;
[0081] Coating a solid electrolyte layer on the surface of the carbon-coated lithium-rich manganese-based material:
[0082] By weight, 105 parts of carbon-coated lithium-rich manganese-based material, 7 parts of lithium hydroxide, 3 parts of titanium sulfate, 1.5 parts of lanthanum nitrate, and 0.9 parts of chromium sulfate are taken;
[0083] After mixing the carbon-coated lithium-rich manganese-based material and water, ultrasonically disperse them at an ultrasonic frequency of 65 kHz for 50 minutes, then add 3% of the mass of the lithium-rich manganese-based material, acetylene black, and 1.3% of the mass of the lithium-rich manganese-based material, carboxymethyl cellulose, and stir and mix them for 60 minutes at a temperature of 68° C. and a speed of 500 r / min with a stirrer to obtain a main material suspension with a concentration of 110 g / L;
[0084] The D50 of the acetylene black is 22 nm;
[0085] Dissolving lithium hydroxide in water to obtain a lithium hydroxide solution with a mass fraction of 9%;
[0086] Add titanium sulfate, lanthanum nitrate and chromium sulfate into water with a mass 12 times that of titanium sulfate, stir and dissolve to obtain a mixed solution;
[0087] The mixed solution is added to the main material suspension, stirred and mixed with a stirrer at a speed of 300 r / min for 30 minutes, and then lithium hydroxide solution is added. The mixture is heated and stirred at a temperature of 80°C and a stirring speed of 600 r / min for reaction for 2 hours, and then kept warm and allowed to stand for 2 hours. The filter cake is collected by suction and washed with deionized water 4 times, dried, and then kept warm and reacted for 5 hours in a nitrogen atmosphere at a temperature of 720°C. The mixture is cooled and discharged to obtain a solid electrolyte and carbon composite coated lithium-rich manganese-based positive electrode material.
[0088] Example 3
[0089] Lithium-rich manganese-based materials coated with island-shaped carbon composite layers:
[0090] By weight, take 120 parts of anhydrous ethanol, 6 parts of glycerol, 6 parts of aluminum nitrate, 0.6 parts of conductive carbon, and 45 parts of lithium-rich manganese-based material;
[0091] Wherein, the conductive carbon includes the following raw materials in parts by weight:
[0092] 40 parts Super P, 10 parts single-walled carbon nanotubes, 6 parts graphene oxide;
[0093] The D50 of the Super P is 50 nm;
[0094] The single-walled carbon nanotube has an aspect ratio of 4000 and a length of 6 μm;
[0095] The D50 of the graphene oxide is 350nm;
[0096] The D50 of the lithium-rich manganese-based material is 5 μm;
[0097] The lithium-rich manganese-based material is a quasi-spherical particle, and the sphericity of the lithium-rich manganese-based material is 8.8;
[0098] First, anhydrous ethanol and glycerol are mixed evenly, and then aluminum nitrate is added. After stirring and dissolving, conductive carbon is added. After ultrasonic dispersion for 4 hours at an ultrasonic frequency of 120kHz and a temperature of 40°C, a lithium-rich manganese-based material is added. Subsequently, the mixture is heated and stirred at a temperature of 75°C and a stirring speed of 400r / min for concentration to volatilize the anhydrous ethanol, thereby obtaining a concentrated material.
[0099] The concentrated material was transferred into a carbonization furnace, and heated at a heating rate of 5°C / min under nitrogen protection. After continuous calcination at 550°C for 6 hours, the material was cooled to room temperature with the furnace, and the calcined material was obtained.
[0100] The calcined material and a 4% strong alkali solution were mixed at a mass ratio of 1:10, and ultrasonically reacted for 15 minutes at a temperature of 60°C and an ultrasonic frequency of 65kHz;
[0101] Wherein, the strong alkaline solution is selected from potassium hydroxide solution;
[0102] After the ultrasonic reaction is completed, washing with deionized water until the washing liquid is neutral, and drying to obtain a carbon-coated lithium-rich manganese-based material;
[0103] Coating a solid electrolyte layer on the surface of the carbon-coated lithium-rich manganese-based material:
[0104] By weight, 110 parts of carbon-coated lithium-rich manganese-based material, 8 parts of lithium hydroxide, 4 parts of titanium sulfate, 2 parts of lanthanum nitrate, and 1.2 parts of chromium sulfate are taken;
[0105] After mixing the carbon-coated lithium-rich manganese-based material and water, ultrasonically disperse them at an ultrasonic frequency of 65 kHz for 60 minutes, then add 4% of the mass of the lithium-rich manganese-based material, acetylene black, and 1.4% of the mass of the lithium-rich manganese-based material, carboxymethyl cellulose, and stir and mix them for 60 minutes at a temperature of 70° C. and a rotation speed of 500 r / min with a stirrer to obtain a main material suspension with a concentration of 120 g / L;
[0106] The D50 of the acetylene black is 25 nm;
[0107] Dissolving lithium hydroxide in water to obtain a lithium hydroxide solution with a mass fraction of 10%;
[0108] Add titanium sulfate, lanthanum nitrate and chromium sulfate into water with a mass 15 times that of titanium sulfate, stir and dissolve to obtain a mixed solution;
[0109] The mixed solution is added to the main material suspension, stirred and mixed with a stirrer at a speed of 300 r / min for 30 minutes, and then lithium hydroxide solution is added. The mixture is heated and stirred at a temperature of 80°C and a stirring speed of 600 r / min for reaction for 2 hours. The mixture is kept warm and allowed to stand for 2 hours. The filter cake is collected by suction and washed with deionized water for 5 times, dried, and then kept warm and reacted for 6 hours in a nitrogen atmosphere at a temperature of 750°C. The mixture is cooled and discharged to obtain a solid electrolyte and carbon composite coated lithium-rich manganese-based positive electrode material.
[0110] Example 4
[0111] The present embodiment differs from the embodiment 1 in that graphene oxide is not added to the conductive carbon, and the other conditions remain unchanged.
[0112] Example 5
[0113] The difference between this embodiment and embodiment 1 is that the D50 of graphene oxide is 60 nm, and the other conditions remain unchanged.
[0114] Example 6
[0115] The present embodiment is different from the embodiment 1 in that the sphericity of the lithium-rich manganese-based material is 8.4, and the other conditions remain unchanged.
[0116] Example 7
[0117] Compared with Example 1, the present embodiment differs in that acetylene black is not added, and other conditions remain unchanged.
[0118] Comparative Example 1
[0119] Compared with Example 1, this comparative example has the following differences:
[0120] Lithium-rich manganese-based materials coated with a continuously distributed carbon composite layer:
[0121] By weight, take 100 parts of anhydrous ethanol, 4 parts of glycerol, 4 parts of aluminum nitrate, 0.4 parts of conductive carbon, and 38 parts of lithium-rich manganese-based material;
[0122] Wherein, the conductive carbon includes the following raw materials in parts by weight:
[0123] 30 parts Super P, 8 parts single-walled carbon nanotubes, 4 parts graphene oxide;
[0124] The D50 of the Super P is 40 nm;
[0125] The single-walled carbon nanotube has an aspect ratio of 3500 and a length of 4 μm;
[0126] The D50 of the graphene oxide is 300 nm;
[0127] The D50 of the lithium-rich manganese-based material is 3 μm;
[0128] The lithium-rich manganese-based material is a quasi-spherical particle, and the sphericity of the lithium-rich manganese-based material is 8.6;
[0129] First, anhydrous ethanol and glycerol are mixed evenly, and then aluminum nitrate is added. After stirring and dissolving, conductive carbon is added. Under the conditions of ultrasonic frequency of 100kHz and temperature of 35°C, ultrasonic dispersion is performed for 2 hours, and then lithium-rich manganese-based materials are added. Subsequently, the mixture is heated and stirred at a temperature of 70°C and a stirring speed of 400r / min to concentrate the mixture so that the anhydrous ethanol is volatilized to obtain a concentrated material.
[0130] The concentrated material is transferred into a carbonization furnace, and heated at a heating rate of 3°C / min under nitrogen protection. After continuous calcination at 500°C for 4 hours, the material is cooled to room temperature with the furnace, and the calcined material is obtained, which is a carbon-coated lithium-rich manganese-based material.
[0131] The rest of the conditions remain unchanged.
[0132] The performance tests were performed on the products obtained in the above examples and comparative examples. The specific test methods and test results are as follows:
[0133] LLMO, acetylene black and PVDF were weighed in a mass ratio of 8:1:1 and dry-grinded for 6 minutes, and then an appropriate amount of N-methylpyrrolidone was dripped into the grinding material until it became viscous. Then it was evenly coated on a 12μm aluminum foil and placed in a vacuum drying oven at 110℃ for 6h. The dried pole piece was punched into a circular piece with an aperture of 12mm using a tablet press, and assembled into a CR2025 button cell in a glove box with the positive and negative electrode shells, Celgard-2500 polypropylene microporous diaphragm, nickel mesh current collector and 1mol / L LiPF6 dissolved EC+DMC+DMC (volume ratio of 1:1:1) mixed electrolyte. The charge and discharge test was carried out at a temperature of 25℃ in the Xinwei CT-4008 constant temperature battery test system.
[0134] First, the initial discharge capacity of the battery is tested at a rate of 0.1C;
[0135] Then, the corresponding charge and discharge test is performed within the working voltage range of 2.0V-4.5V;
[0136] The charge and discharge tests were carried out at 1C and 3C rates respectively to test the capacity retention rate after 150 cycles. The detailed test results are shown in Table 1.
[0137] Table 1: Product performance test results
[0138]
[0139] It can be seen from the test results in Table 1 that the product obtained by the present invention has better capacity performance and higher capacity retention rate when performing high-rate charge and discharge.
[0140] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for synthesizing a solid electrolyte and carbon composite coated lithium-rich manganese-based positive electrode material, characterized in that: The specific synthesis steps include: Lithium-rich manganese-based materials coated with island-shaped carbon composite layers: By weight, take 100-120 parts of anhydrous ethanol, 4-6 parts of glycerol, 4-6 parts of aluminum nitrate, 0.4-0.6 parts of conductive carbon, and 38-45 parts of lithium-rich manganese-based material; First, mix anhydrous ethanol and glycerin evenly, then add aluminum nitrate, stir and dissolve, then add conductive carbon, ultrasonically disperse evenly, then add lithium-rich manganese-based material, heat and stir to concentrate, so that the anhydrous ethanol evaporates, and obtain concentrated material; The concentrated material is transferred into a carbonization furnace, and calcined for 4-6 hours at a temperature of 500-550°C under nitrogen protection, and then cooled and discharged to obtain a calcined material; The calcined material is subjected to ultrasonic reaction with a strong alkaline solution, washed with water, and dried to obtain a carbon-coated lithium-rich manganese-based material; Coating a solid electrolyte layer on the surface of the carbon-coated lithium-rich manganese-based material: By weight, 100-110 parts of carbon-coated lithium-rich manganese-based material, 6-8 parts of lithium hydroxide, 3-4 parts of titanium sulfate, 1-2 parts of lanthanum nitrate, and 0.8-1.2 parts of chromium sulfate are taken; Mixing and dispersing the carbon-coated lithium-rich manganese-based material and water to obtain a main material suspension with a concentration of 100-120 g / L; Dissolving lithium hydroxide in water to obtain a lithium hydroxide solution with a mass fraction of 8-10%; Add titanium sulfate, lanthanum nitrate and chromium sulfate into water with a mass 10-15 times that of titanium sulfate, and stir to dissolve to obtain a mixed solution; The mixed solution is added to the main material suspension, mixed evenly, and then lithium hydroxide solution is added. After heating and stirring for reaction, the mixture is kept warm and allowed to stand, filtered, washed and dried. After being kept warm for 4-6 hours at 700-750°C in a nitrogen atmosphere, the mixture is cooled and discharged to obtain a solid electrolyte and carbon composite coated lithium-rich manganese-based positive electrode material.
2. The method for synthesizing a solid electrolyte and carbon composite coated lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The conductive carbon comprises the following raw materials in parts by weight: 30-40 parts Super P, 8-10 parts single-walled carbon nanotubes, 4-6 parts graphene oxide.
3. The method for synthesizing a solid electrolyte and carbon composite coated lithium-rich manganese-based positive electrode material according to claim 2, characterized in that: The D50 of the Super P is 40-50nm; The single-walled carbon nanotube has an aspect ratio of 3500-4000 and a length of 4-6 μm; The D50 of the graphene oxide is 300-350nm; The D50 of the lithium-rich manganese-based material is 3-5 μm.
4. The method for synthesizing a solid electrolyte and carbon composite coated lithium-rich manganese-based positive electrode material according to claim 3, characterized in that: The lithium-rich manganese-based material is a quasi-spherical particle, and the sphericity of the lithium-rich manganese-based material is 8.6-8.
8.
5. The method for synthesizing a solid electrolyte and carbon composite coated lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The method of subjecting the calcined material to ultrasonic reaction with a strong alkaline solution comprises: The calcined material and the strong alkali solution with a mass fraction of 2-4% are mixed at a mass ratio of 1:8-10, and ultrasonically reacted for 10-15 minutes at a temperature of 40-60°C and an ultrasonic frequency of 60-65kHz; Wherein, the strong alkaline solution is selected from any one of sodium hydroxide solution or potassium hydroxide solution.
6. The method for synthesizing a solid electrolyte and carbon composite coated lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The main material suspension also includes acetylene black in an amount of 2-4% by weight of the lithium-rich manganese-based material, and the D50 of the acetylene black is 20-25 nm.
7. The method for synthesizing a solid electrolyte and carbon composite coated lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The main material suspension also includes 1.2-1.4% of the mass of the lithium-rich manganese-based material, carboxymethyl cellulose.
Citation Information
Patent Citations
Coating modification method of lithium-rich manganese-based positive electrode material
CN111740085A
Silicon-carbon negative electrode composite material with porous structure as well as preparation method and application of silicon-carbon negative electrode composite material
CN114551850A
Method for modifying lithium-rich manganese-based positive electrode material by molybdenum carbide heterojunction coating
CN117602684A
Double-layer coated hollow silicon-carbon negative electrode material and preparation method thereof
CN117727907A
Modified lithium-rich manganese-based lithium ion battery positive electrode material and preparation method thereof
CN119029199A
